The influence of emotional intelligence on employee’s performance / Zamharirah Mohd Khairi - Mohd Khairi, Zamharirah (Faculty of Business and Management, 2019)
Employee performance is important role in organization as it is a critical factor for organization success. In addition, unperformed employees will somehow impact the organization in order to achieve their targets and goals. Therefore, this study seeks to examine factors that can influence employee performance. This study focuses on several factors that can influence of emotional intelligence on employee performance such as self-awareness, self-management and social awareness. The objective of this study is to identify the factors of emotional intelligence that affecting employee performance in Pejabat Majlis Daerah Tampin. The sampling technique that was used in this study is convenient sampling and the data collection was used is self-administered questionnaire. The researcher has distributed 103 questionnaires to 103 of the respondents, then get the return questionnaire of 87 of the respondents. The data that had been collected was then evaluated by using Statistical Package for the Social Science (SPSS) Software version 22. Then, using SPSS test that were converged such as reliability analysis, frequency analysis, descriptive analysis, Pearson’s correlation analysis and multiple regression. The findings of the study revealed that all independent variables were found to have significant relationships with dependent variable which is employee performance.